Mechanistic insights into a copper-disulfide interaction in oxidation of imines by disulfides - Srogl, Jiri; Hývl, Jakub; Révész, Agnes; Schröder, Detlef (Chemical communications (Cambridge, England), 2009)
The concept of using disulfides as an oxidant for Cu(i) is introduced as part of a Cu-catalyzed process leading to the formation of benzothiazole from an iminodisulfide under an inert atmosphere.